Perspectiva comparativa de las llamadas guerras sucias en América Latina y México - Cedillo, Adela (El Colegio de México, A.C., 2024)
This article compares the cases of Brazil, Chile and Argentina –countries that experienced military coups, dictatorships, armed insurgencies and state terror in the sixties and seventies– with that of Mexico, where similar phenomena occurred, despite the country’s revolution that did away with military coups. The aspects emphasized in this comparative analysis are the political system, armed underground organizations, counterinsurgency and its death toll, the struggle for human rights and memory. It also includes a description of the Mexican Operation Condor –focused on the elimination of drug cultivation– in order to emphasize its similarities with its South American counterpart in spite of their lack of an organic connection. The general argument is that a comparative perspective offers a new angle from which to understand the causes and escalation of political violence in cases that have not been considered to be analogous by examining the juxtaposition of local, transnational and global contexts. This article is based on archival research, the contemporary press, interviews, official reports and secondary sources.